Primary Anterior Thoracic Wall Abscess with Osteomyelitis by Salmonella paratyphi A: Case Report - Murthy, Neetha S.; Mahale, Rashmi P.; MVS, Krishna Karthik (Journal of Laboratory Physicians, 2023)
Salmonella enterica serovar Typhi and Paratyphi have been imputed in the causation of enteric fever. Cardiovascular and extraintestinal Salmonella infections have been documented among immunocompromised individuals. Rarely these pathogens are ascribed in the causation of extraintestinal infections among immunocompetent hosts due to hematogenous seeding. We report a case of anterior chest wall abscess with osteomyelitis in an immunocompetent adult by Salmonella paratyphi A without any prior predisposing conditions or gastrointestinal symptoms. The patient underwent incision and drainage of the loculated pus and the involved costochondral junction was curetted. Medical management was guided by automated antibiotic susceptibility testing. Patient responded well to treatment and was discharged with no residual morbidities. Prompt diagnosis complements appurtenant treatment and thereby averts defunct consequential sequelae.
Keywords: Salmonella paratyphi A; extraintestinal salmonellosis